Propostas de estruturação e organização do trânsito visando minimizar os acidentes no município de Tailândia-PA - MACEDO, Fabiana Schneider de (2018)
The city of Tailândia-Pa is constantly growing population, and with it grows the number of motor vehicles in the city. With this rapid growth, the city meet the criterion of decentralization of traffic, the emerging need to implement improvements in the road system. This work aims to evaluate and diagnose the conditions of transit of Tailândia to propose changes in its organization and structure in order to reduce the accident rate. For this purpose, we performed a literature search on the topic of traffic and the process of decentralization. Later came a field study to characterize the major traffic problems and compute the volume and composition of traffic at two major intersections in the city. As a result characterized several problems that make the environment chaotic traffic, disregard for traffic laws, potholed roads, sidewalks, busy or unavailable, lack of control of the body responsible. There was a high rate of motorcycles, representing 37.52% of the traffic mix in the two crosses analyzed, and this is the type of vehicle you have less control, the low percentage of licensing, and their drivers are the ones that more flout traffic laws. The proposed measures were based on the elements that make up the traffic environment: the road system, man and institution. For the municipal transit propose the creation of two departments: urban mobility, to address the problems of accessibility and mobility, and control division of violation and levying fines. It also highlights the need for training of staff, this being one of the biggest problems of the region, as well as the implementation of necessary infrastructure for planning and operation of transit. It is proposed to create a database to record accidents, and deployments are suggested measures legislation, education and engineering, especially in the downtown area, where the highest number of accidents. It is worth noting that these actions will only be effective in reducing accidents to society as a whole is committed to making the environment more organized and safe traffic.